(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The dominant causal agents of plant diseases are fungi. Diverse strategies are used by plant pathogenic fungi to colonize plants and cause disease in them. Plant pathogenic fungi play important role in agriculture. They infect the cereal crops especially in stored condition. The present study was conducted with the main purpose to screen the fungal contamination on Zea mays seeds. Zea mays seeds were surface sterilised with 0.2% aqueous sodium hypochlorite and arranged on blotters to screen fungal contamination by standard blotting method. The fungal isolates were isolated from the collected seeds after 7 days. Identification of fungi was done by direct microscopy and molecular techniques such as DNA sequencing. Results revealed that Aspergillus niger was the most common isolate from Zea mays. Identification of fungi by molecular method using Polymerase Chain Reaction (PCR) helped in the confirmation of fungal species with precision and in the least possible time. In conclusion, the isolated species of fungi were identified morphologically as Aspergillus niger. The fungal samples were then identified through molecular techniques by DNA sequencing were identified as Aspergillus niger.